2015
DOI: 10.1002/lary.25531
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the nasal cavity: A population‐based analysis

Abstract: 4. Laryngoscope, 126:560-565, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 26 publications
2
41
0
2
Order By: Relevance
“…patients. This is in line to former studies demonstrating that nodal involvement represents a significantly worse prognostic factor that cut patients’ overall survival almost to a half compared to node-negative patients [10, 19]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…patients. This is in line to former studies demonstrating that nodal involvement represents a significantly worse prognostic factor that cut patients’ overall survival almost to a half compared to node-negative patients [10, 19]. …”
Section: Discussionsupporting
confidence: 92%
“…In the meta-analysis of Scurry et al, reviewing 23 studies, the risk for regional recurrence was 18.1%, and therefore, they favor elective regional treatment [11]. Conversely, other authors recommend elective treatment only for T4 tumors [10]. However, according to Ahn et al, elective nodal treatment could lead to a five- to sixfold decrease of nodal recurrence in sinonasal carcinomas [2].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that other common small round cell malignant tumors, such as lymphoma and rhabdomyosarcoma, can be differentiated from SCCs by measurements of ADC values, revealing that D values of DKI may also be useful in the discrimination of ONBs and SCCs. However, we found no significant differences between these two entities, perhaps because SCC is also a common type of sinonasal malignant tumor with densely packed tumor cells, which may restrict water diffusion . Furthermore, there existed a considerable overlap of D values between ONBs and SCCs, which may be another possible reason to interpret no significant difference of D values between the two entities and that need to be further verified with a larger sample size.…”
Section: Discussionmentioning
confidence: 56%
“…However, we found no significant differences between these two entities, perhaps because SCC is also a common type of sinonasal malignant tumor with densely packed tumor cells, which may restrict water diffusion. 27 Furthermore, there existed a considerable overlap of D values between ONBs and SCCs, which may be another possible reason to interpret no significant difference of D values between the two entities and that need to be further verified with a larger sample size. Notably, in this study the mean K value of ONBs was found to be significantly higher than that of SCCs, revealing that the internal microstructure of ONBs was more complex than that of SCCs.…”
Section: Discussionmentioning
confidence: 95%
“…[8] Recently, accumulating evidence suggests that a number of genetic alterations may contribute to the initiation and progression of SNSCC. [912] The p53 gene is a tumor suppressor gene mapped to chromosome 17p13, encodes the p53 protein, which involves in the regulation of the cell cycle, the inhibition of DNA synthesis, the function of DNA repair and apoptosis.…”
Section: Introductionmentioning
confidence: 99%